Validity and reliability of Patient-Reported Outcomes Measurement Information System (PROMIS) Instruments in Osteoarthritis - Broderick, Joan E. (2013)
OBJECTIVE: Evaluation of known group validity, ecological validity, and test-retest reliability of four domain instruments from the Patient Reported Outcomes Measurement System (PROMIS) in osteoarthritis (OA) patients. METHODS: Recruitment of an osteoarthritis sample and a comparison general population (GP) through an Internet survey panel. Pain intensity, pain interference, physical functioning, and fatigue were assessed for 4 consecutive weeks with PROMIS short forms on a daily basis and compared with same-domain Computer Adaptive Test (CAT) instruments that use a 7-day recall. Known group validity (comparison of OA and GP), ecological validity (comparison of aggregated daily measures with CATs), and test-retest reliability were evaluated. RESULTS: The recruited samples matched (age, sex, race, ethnicity) the demographic characteristics of the U.S. sample for arthritis and the 2009 Census for the GP. Compliance with repeated measurements was excellent: > 95%. Known group validity for CATs was demonstrated with large effect sizes (pain intensity: 1.42, pain interference: 1.25, and fatigue: .85). Ecological validity was also established through high correlations between aggregated daily measures and weekly CATs (≥ .86). Test-retest validity (7-day) was very good (≥ .80). CONCLUSION: PROMIS CAT instruments demonstrated known group and ecological validity in a comparison of osteoarthritis patients with a general population sample. Adequate test-retest reliability was also observed. These data provide encouraging initial data on the utility of these PROMIS instruments for clinical and research outcomes in osteoarthritis patients.